Eksplorasi Faktor yang Mempengaruhi Minat Pembelian Gacha pada Game Online - Devin Prayogo; Diah Priharsari; Andi Reza Perdanakusuma (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
With the increasingly rapid spread of smartphones, mobile gaming applications are increasing all over the world. Games finally began to develop and emerged called online games. Online games are electronic games that are connected to the internet network that are played through various game devices, and can be played by many users at the same time. Although it can be played for free, players can use their in-game money to improve their gaming experience. Players can buy items that make the game faster to level up, or get limited items to improve the playing experience. Because many people spend their money to make in-game purchases, a feature called gacha appears. Players can buy the gacha using a certain amount of money or so-called top-ups. From buying gacha, players will get prizes at random, with different levels of prize rarity, that's why people call it similar to gambling and sweepstakes. Gacha seems to motivate and trigger the desire to buy players so that players spend more money on gacha in the game even though the price and percentage of wins for rare prizes are determined by the game provider. The purpose of this study is to find out what are the factors in purchasing gacha in online games, and the influence of gacha in the experience of playing online games. This research, the author uses a qualitative method.